Motor control learning: What is the brain doing to provide and maintain high performance to sensorimotor systems - Gauthier, G. M.; Bourdin, C.; Blouin, J. (12th Annual Congress of the European College of Sport Science, Jyväskylä, Finland - July 11-14th 2007, 2007)
When we use for the first time a tennis racket (or any hand tool) our brain must take into account the kinematics and kinetics of the racket to precisely hit a ball. Over time, the brain develops a new sensory-to-motor transformation. The same processes may be activated when we act on and in the surrounding world indirectly through intervening processes such as optical devices, powered tools and more refined means of telemanipulation, or when lesions affect neuromuscular or central nervous systems. This functional modification of the sensorimotor system input/output relationship is the result of the activation of a specific control process: the adaptive control. Several laboratories have studied this control for years in systems whose principal information of control is vision. Still, there is no general agreement as to how earlier cybernetics and neuroanatomical models describing adaptative control can be conciliated to more recent conceptual models featuring "internal models". Another matter of interest for researchers in the motor control field relates to the interpretation and modelling of a phenomenon observed when an observer (or an operator) is submitted alternately to a normal situation and a situation requiring adaptation (for example vision through glasses or no glasses). The phenomenon can be observed, as we did, in experiments carried out on subjects submitted to repeated series of hand pointing to visual targets seen through side deviating prisms. The now classical paradigm, conducted over several days, shows that the prismatic effect (the error observed when pointing is carried out through the prisms with vision of the hand) measured at the beginning of the second experiment is weaker than in the first experiment, and total adaptation (expressed as the inverse of the remaining error after several pointings with vision of the hand) at the end of a training session is obtained more quickly, while the consecutive effect (error after the prisms are removed) is weaker. With the passing days, the cumulative effect of training continues, so that after some days, the observer correctly locates the targets with the hand, even when the latter is not visible whether the task is carried out with or without the prisms. It appears as if the observer has developed two visuo-manual relationships, one for the condition of normal vision and the other for the condition of vision through the prisms. We call it duo-mode adaptation. The discussion will bear on this later phenomenon. Besides, arguments from recent and earlier experiments will be presented to support the idea that a common comprehensive model may be drawn to describe the adaptive processes that develop in response to the use of new hand controlled devices, the use of progressively deteriorating tools and the alternate use of two similar but yet different sports supplies, mechanical tools, or optical devices (for example, tennis racket and table tennis paddle; far and near sight pairs of glasses, etc.).